Matematika Lingkungan Berbasis Budaya Berbantu Microsoft Whiteboard - Ema Butsi Prihastari; Ratna Widyaningrum (MENDIDIK: Jurnal Kajian Pendidikan dan Pengajaran, 2022)
The importance of environmental insights and skills that must be mastered for 21st century proficiency go hand in hand in this era of digitalization. On the one hand, technological developments indirectly make lecturers to equip skills for their students in utilizing IT in mathematics learning, especially blended learning. One of the mathematics courses that can be integrated with environmental insight mathematics is Geometry and Measurement. Geometry is associated with historical heritage buildings (Pasar Gede) as a source of contextual learning that is a reality with everyday life. The purpose of this study is to find out the application of culture-based environmental mathematics with the help of Microsoft whiteboard in students. The research method used in this study is descriptive research. The research location is the PGSD UNISRI Study Program. The data collection techniques used are observation, interview, and documentation. Data analysis using data reduction, display data, conclusion drawing/verification. The validity of the data uses triangulation methods. The results of the study were obtained so that there was an increase in learning by implementing learning strategies consisting of: a) preparing learning plans, b) preparing activity steps, and c) designing learning evaluations to assess appropriate cognitive, affective, and psychomotor aspects.